MOTIF PENGGUNAAN INSTAGRAM SEBAGAI REFERENSI WISATA (Studi Khusus pada Mahasiswa Fisip Unisri Surakarta) - Buddy Riyanto, Krisna Adji Baskara, Bedjo Sukarno & (Transformasi, 2017)
This research is descriptive qualitative which trying to described the motive of the use ofinstagram as a tourism reference on students of UNISRI Surakarta. With using analysis displayat the interactive model by miles and huberrman, the results of this research pointed out that themotive of the use of instagram among FISIP students are varied, there are students that justopen, see, and uploaded a picture or photos on instagram, there are also students who accessinstagram to seek for information, there are also students who access to find reference tourismin Instagram acounts.keywords: motives, instagram, tourism reference